Analisis Nilai Moral dan Nilai Sosial dalam Novel Manusia dan Badainya Karya Syahid Muhamad serta Pemanfaatannya sebagai Bahan Ajar di SMA - Sihabudin, Sihabudin; Trisnawati, Trisnawati; Maulana, Nanang (Jurnal Artikula, 2024)
This research aims to describe the moral values ​​in the novel Man and the Storm by Syahid Muhamad, describe the social values ​​in the novel Man and the Storm by Syahid Muhamad, and utilize moral values ​​and social values ​​in the study of literature in high school. This research is qualitative descriptive research, namely collecting, analyzing, using qualitative analysis techniques, namely Analysis of Moral Values ​​and Social Values ​​in the novel Man and his Storm by Syahid Muhamad and its use as teaching material in high school. The data source is the novel Man and his Storm by Syahid Muhamad. Publication year 2022 published by Gradien Mediatama with 248 pages. The approach taken in analyzing this research data uses a sociological approach with a Content Analysis content analysis strategy. The moral values ​​found in the novel consist of 6 honest values. Be yourself 11 quotes. Responsible for 4 quotes. Independence as many as 6 quotes. Moral courage as many as 7 quotes. Humility as many as 8 quotes. Critical of 7 quotes. Meanwhile, the social values ​​found were the value of love with 11 quotes. Responsibility for 4 quotes. Concern as many as 20 quotes. Empathy as many as 9 quotes. Collaboration with 6 quotes. Please help as many as 5 quotes. As for its relevance to being used as teaching material, the novel is worthy of being used as teaching material at the high school level because: 1) the novel is the work of a famous person in the world of literature, especially prose literary works; 2) the novel is a serious novel; 3) the novel is rich in life values, in this case moral and social values; 4) Suitability as teaching material has been approved by various validators such as lecturers, teachers and students. This study of the novel Man and his Storm by Syahid Muhamad is in accordance with the validation results given to the validator; and 5) learning about the values ​​in a novel is at the high school level. TP.12.5 students assess and criticize the intrinsic elements of characterization, plot, story, setting, and depiction of society in the novel.